Exploring the Effectiveness of Integrated Care Models for Managing Mental Health Issues - Adindu, Kelechi Nelson; Akubuiro, Christiana Onyinyechi; Onochie, Emeka Darlington; Nwonye, Uchenna Chritiana; Adesina, Oluwagbemiga; Otaniyen, Patience Nkese; Okorie, Chukwuka David (British Journal of Healthcare and Medical Research, 2024)
The global rise in mental health issues has exposed limitations in conventional healthcare systems' ability to deliver comprehensive and integrated care for individuals with complex mental disorders. In response, integrated care models have emerged as promising solutions, combining primary healthcare, specialized mental health services, and social support networks. This research investigates the efficacy of these integrated approaches in addressing mental health concerns, with a particular focus on their capacity to enhance care accessibility, improve patient outcomes, and elevate overall service quality. The study examines various integration models, such as collaborative care and patient-centered medical homes, to assess their impact on reducing healthcare fragmentation, enhancing care continuity, and promoting holistic treatment strategies. Research methods include systematic reviews of existing literature, case studies, and interviews with both healthcare professionals and patients. Conclusively, the study's findings aim to consolidate insights from contemporary research and practical examples to determine optimal practices and obstacles in deploying integrated care for mental health treatment. Furthermore, it delves into the prospects of cutting-edge technologies and cross-disciplinary partnerships to boost the effectiveness of these frameworks. Ultimately, this research seeks to contribute to the development of more effective, person-centered mental health care systems.